Defective Interferon Gamma Production by Tumor-Specific CD8+ T Cells Is Associated With 5′Methylcytosine-Guanine Hypermethylation of Interferon Gamma Promoter - Abd Hamid, Megat; Yao, Xuan; Waugh, Craig; Rosendo-Machado, Samara; Li, Chris; Rostron, Timothy; Frankland, John; Peng, Yanchun; Dong, Tao (Frontiers in Immunology, 2020)
Interferon gamma (IFNγ) supports effector responses of CD8+ cytotoxic T lymphocytes (CTL), and a surrogate marker for detection of antigen-specific T cells. Here, we show that tumor-specific CTL clones have impaired IFNγ expression and production upon activation. Assessing the relationship between IFNγ production and the 5’methylcytosine-guanine (CpG) dinucleotide methylation of the IFNγ promoter using bisulphite treatment shown that IFNγ- CTL clones accumulates CpG hypermethylation within the promoter at key transcription factor binding sites (-186 and -54), known to be vital for transcription. We confirmed these findings using ex-vivo isolated and short-term expanded bulk tumor-specific CTL lines from four cancer patients and demonstrated that IFNγ methylation inversely correlates with transcription, protein level and cytotoxicity. Altogether, we propose that human tumor-specific CTLs are deficient in IFNγ response due to hypermethylation of the IFNγ promoter. Our findings have important implications for immunotherapy strategies and for methods to detect antigen-specific T cells.